The Anthropological Dimension of the Experience of God’s Presence and God’s absence - Głaz, Stanisław (Studia Psychologica: Theoria et praxis, 2007)
Human beings in the course of their life have a great variety of experiences. Some of them are linked to everyday events, some can be caused by God. This article presents the scale of religious experience. In order to estimate the intensity of the effects of one’s religious experience (the intensity of the experience of God’s presence and God’s absence) among believers, the author of the paper constructed The Scale of the Effects of Religious Experience (SERE). The scale is made up of six subscales. Factor I is related to the attitude of a person to the others and shows the awareness of changes of one’s own personality caused by the experience of the absence of God (awareness of the change of the attitude to the others) (I-NOB). Factor II is related to the attitude of a person to the others and shows the awareness of changes of one’s own personality caused by the experience of the presence of God (awareness of the changes of the attitude to the others) (I-OB). Factor III is related to the attitude of a person to oneself and shows the awereness of the changes of one’s own personality caused by the awareness of the absence of God (awareness of the change of the attitude to oneself) (JANOB). Factor IV is related to the attitude of a person to oneself and shows the awareness of the chagnes of one’s own personality caused by the experience of the presence of God (awareness of the change of the attitude to oneself) (JA-OB). Factor V is related to the attitude of a person to God and shows the awareness of the changes of one’s own personality casued by the experience of the absence of God (awareness of the change of the attitude to God) (BNOB). Factor VI is related to the attitude of a person to God and shows the awareness of the changes of one’s own personality caused by the experience of the presence of God (awareness of the change of the attitude to God) (B-OB). All the factors have a high coefficience of Cronbach’s alfa (0.90 to 0.97).